2019
DOI: 10.1093/ijlct/ctz047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of strength development of cemented desert soil

Abstract: For highway construction or any superstructure, on dune sand, designers and construction teams must ensure that the foundation soil is stable enough to provide support for the applied loads. Sand dunes are stretched across Libyan deserts that make road construction a challenge because of the poor soil base. Replacement of such a weak soil is very expensive and not economically feasible, and, in many cases, there is no alternative soil nearby. This study used two different mix designs aimed at stabilizing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A precise soil portrayal and grouping is fundamental to the determination of the right materials and methodology. Table 2 records the most reasonable treatments for different soil types to stabilize these soils for various objectives [28].…”
Section: Soil Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise soil portrayal and grouping is fundamental to the determination of the right materials and methodology. Table 2 records the most reasonable treatments for different soil types to stabilize these soils for various objectives [28].…”
Section: Soil Stabilizationmentioning
confidence: 99%
“…Sharo et al [6] demonstrated the adequacy of the expansion of calcium chloride in soil treatment. Amhadi and Assaf [7] utilized calcium oxide as a stabilization technique in clay soils so as to restrain its development contraction properties. Hesami et al [8] utilized coal burning results in rollercompacted solid, roadway, and parking areas.…”
Section: Introductionmentioning
confidence: 99%
“…The process of stabilizing the desert soil with cement decreases its compressibility and its permeability, and it further increases its strength, its bearing capacity, and its durability. It also reduces construction cost by utilizing local materials [20,21]. Furthermore, the use of cement to improve the engineering properties of soils has already been adopted [22][23][24][25], and this is mainly due to the hardening of cement in the presence of moisture and during the curing period [26].…”
Section: Introductionmentioning
confidence: 99%
“…The dunes sand was stabilized by several materials such as bentonite and lime [8], lime and silica fume [9][10], oil residue [11], fibers and geosynthetics [12][13][14], and cement [15][16][17]. The stabilization aimed to improve the performance of dunes sand under structures.…”
Section: Introductionmentioning
confidence: 99%